Progress Report to the International Monetary and Financial Committee on the Activities of the Independent Evaluation Office of the IMF. (Policy Papers; Policy Paper, 2016)
This progress report presents the key conclusions and recommendations of the IEO evaluation of data and statistics at the IMF that was discussed by the Executive Board on March 17, 2016. It also summarizes the IMF's plan, approved by the Board in December 2015, for implementing the recommendations from the IEO evaluation of the IMF Response to the Financial and Economic Crisis and describes the IEO's ongoing work.